Power and Responsibility in Chinese Foreign Policy - Zhang, Yongjin (ANU Press, 2014)
The People's Republic of China is now over fifty years old. Long considered an outsider, or a club of one, in international relations, China has recently become more active in international institutions. Is China becoming a responsible power in global and regional international relations? How accurate is the traditional perception of China? What factors may be motivating the changes in China's approach to international institutions and its perceptions of its own role in the world? There is no certainty that China is becoming a more responsible power, recent developments may be just another manifestation of realpolitik. Power and Responsibility in Chinese Foreign Policy provides a vital insight into these issues, analysing the critical issues in China's international relations- China's regional and global diplomatic and security problems, the changing role of the People's Liberation Army, human rights, religious and democratic movements, and the concept of responsibility. Power and Responsibility in Chinese Foreign Policy is an insightful and vital introduction to all sides of the current debate over China's international relations.